Bathyconchoecia lacunosa (Muller), a rare halocyprid ostracod from the Arabian Sea - James, C Merrylal (MBAI, 1973)
The plankton samples collected during the research cruises of R. V. Varuna along the southwest coast of India in 1963 contained males, females and juvenile specimens of B. lacunosa (Moller), one of the lesser known bathypelagic ostracods, the male of which has remained undescribed. Mailer's (1908) original description of B. lacunosa is also incomplete in some respects being based on a juvenile female obtained at 66° 2/ 9'/ S, 89° 38/ E in the Antarctic waters. This note embodies a redescription of the species based on adult males and females and confirms its earlier record (George, 1967) from Indian Seas.